2005
DOI: 10.1111/j.1538-7836.2005.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

The phospholipid composition and cholesterol content of platelet-derived microparticles: a comparison with platelet membrane fractions

Abstract: Summary. Background: The processes that govern the distribution of molecules between platelets and the microparticles (MP) they release are unknown. Certain proteins are sorted selectively into MP, but lipid sorting has not been studied. Objectives: To compare the phospholipid composition and cholesterol content of platelet-derived MP obtained with various stimuli with that of isolated platelet membrane fractions. Methods: Washed platelets from venous blood of healthy individuals (n ¼ 6) were stimulated with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
88
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 45 publications
10
88
0
1
Order By: Relevance
“…Microparticles contain high amounts of lipid rafts, and these cholesterol-rich membrane microdomains are known to harbor a huge variety of signaling molecules, receptors, and proteases, including the mature form of ADAM17. [39][40][41] Lee and coworkers demonstrated that ADAM17, on its activation by paxillin, the HIV Nef protein, and the polycomb protein Eed, is recruited to extracellular particles. After fusion of these microparticles with blood mononuclear cells, ADAM17-induced TNF-a release from the target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Microparticles contain high amounts of lipid rafts, and these cholesterol-rich membrane microdomains are known to harbor a huge variety of signaling molecules, receptors, and proteases, including the mature form of ADAM17. [39][40][41] Lee and coworkers demonstrated that ADAM17, on its activation by paxillin, the HIV Nef protein, and the polycomb protein Eed, is recruited to extracellular particles. After fusion of these microparticles with blood mononuclear cells, ADAM17-induced TNF-a release from the target cells.…”
Section: Discussionmentioning
confidence: 99%
“…For the construction of standard curves phospholipids of defined composition were used (33% PS and 67% PC). Interestingly, recent studies showed that the phospholipid composition of circulating procoagulant MPs varies depending on type of originating cell and type of stimulation [36][37][38]. Therefore, great variations of the PS and PC distribution on the surface of circulating MPs of different origin may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Adam Ceroi, [1][2][3][4] Fanny Angelot Delettre, [1][2][3][4] Charline Marotel, [1][2][3] Thierry Gauthier, [1][2][3][4] Afag Asgarova, [1][2][3] Sabéha Biichlé, [1][2][3][4] Anne Duperrier, [1][2][3] Guillaume Mourey, [1][2][3] Sylvain Perruche, [1][2][3][4] Laurent Lagrost, [4][5][6][7] David Masson, [4][5][6][7] …”
Section: Letters To the Editormentioning
confidence: 99%
“…Since MP contain potential cholesterol-derived LXR ligands, 6 we evaluated LXR activation in PDC after MP coculture. PMP or EMP were previously reported to exert anti-or pro-inflammatory effects, respectively.…”
mentioning
confidence: 99%